Aplicação do sistema de gestão da qualidade das boas práticas de fabricação (BPF) no Brasil em empresas em produtos para a saúde - Zotelli, Maroá Schaaf (2012)
The certification in quality system to the Good Manufacturing Practices is a requirement of federal health surveillance agency (ANVISA) to ensure the safety, quality and efficacy of medical products through standardization of processes for all manufacturers or distributors of products health that operate in the Brazilian market. With the growth of the production of products for health, the regulated sector seems to face problems concerning the long times of proceedings regulated by ANVISA. This study was based on questionnaires sent to industries of health products in order to analyze the regulatory processes involved in the quality system and product registration recommended by the Good Manufacturing Practices (GMP) for health products, as legislation RDC-59/00. This law is applicable only to health products, also called correlated, and was those used in offices, clinics, hospitals and other health services, such as pressure vessels, pots collection universal equipment for radiography, MRI tomography and magnetic equipment. Thus, the processes were analyzed using multiple choice questions that sought to position the vision of the regulated sector, exposing the problems encountered. A kind of exploratory research has been created, a questionnaire with multiple choice questions, seeking profiling and feedback from respondents. The questionnaire has been administered to thirty-six companies, while the regulated sector, seeking to demonstrate their experience in relation to the services provided by the sector regulator. Overall, 72% of questioned companies answered that they are dissatisfied with the services provided by ANVISA.